Effect of amylose content in morphological, functional and emulsification properties of OSA modified corn starch. (December 2019) - Lopez-Silva, Madai; Bello-Perez, Luis A.; Agama-Acevedo, Edith; Alvarez-Ramirez, Jose
Abstract: Octenyl succinic starch esters were prepared from three corn starches with different amylose content; namely, waxy (5.43%), normal (25.16%) and Hylon VII (65.84%). The degree of substitution varies from 0.0103 for waxy starch to 0.0125 for Hylon VII, meaning that the degree of substitution is positively correlated with the amylose content. Scanning electron microscopy images showed that the esterification reaction affected only the granule surface while leaving the integrity of the granules. Solubility and water retention capacity were increased with the OSA modification, with the effect more pronounced for higher amylose contents. X-ray analysis revealed that the crystallinity type was not affected by esterification. FTIR analysis corroborated the changes in the hydrated and ordered structures of starch granules. Emulsification tests showed that octenyl succinic starch ester was an effective emulsifier for stabilization of oil-in-water emulsions. In particular waxy and Hylon VII starches induced high stabilization degrees as revealed by long-term stability of oil-in-water emulsions. Graphical abstract: Image 1 Highlights: Amylose content plays the central role in OSA esterification of starch granules. OSA esterification occurred mainly on amorphous regions. Esterification improved the emulsifying capacity of modified starch granules.